2019
DOI: 10.3390/cells8020195
|View full text |Cite
|
Sign up to set email alerts
|

Tankyrase (PARP5) Inhibition Induces Bone Loss through Accumulation of Its Substrate SH3BP2

Abstract: There is considerable interest in tankyrase because of its potential use in cancer therapy. Tankyrase catalyzes the ADP-ribosylation of a variety of target proteins and regulates various cellular processes. The anti-cancer effects of tankyrase inhibitors are mainly due to their suppression of Wnt signaling and inhibition of telomerase activity, which are mediated by AXIN and TRF1 stabilization, respectively. In this review, we describe the underappreciated effects of another substrate, SH3 domain-binding prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 92 publications
(172 reference statements)
0
35
0
Order By: Relevance
“…ous studies have reported that Tankyrase inhibition upregulate SH3BP2 1,4 , thus we examined gene expression of SH3BP2 in hBMSCs. Treatment with XAV-939 (3 µM) induced a significant upregulation in SH3BP2 gene…”
Section: Xav-939 Promoted Osteoblast Differentiation Of Hmscs Via Accmentioning
confidence: 99%
See 3 more Smart Citations
“…ous studies have reported that Tankyrase inhibition upregulate SH3BP2 1,4 , thus we examined gene expression of SH3BP2 in hBMSCs. Treatment with XAV-939 (3 µM) induced a significant upregulation in SH3BP2 gene…”
Section: Xav-939 Promoted Osteoblast Differentiation Of Hmscs Via Accmentioning
confidence: 99%
“…Tankyrase is part of poly (ADP-ribose) polymerase (PARPs) superfamily of 17 physiological human PARPs required for numerous cellular and molecular processes 1 3 including glucose metabolism, mitosis 4 , DNA damage repair 5 , genome stability 6 , cellular stress signaling 7 , signal transduction 6 , gene transcription 8 , telomere maintenance, and Wnt signaling 3 . Tankyrases are also promising drug targets that may be useful in several diseases affecting multiple organs 9 , 10 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…From this standpoint, tankyrase can be a therapeutic target to modulate SH3BP2 protein expression. Tankyrase is a poly(ADP-ribose) polymerase that directly binds to SH3BP2 protein and subsequently mediates its degradation [22,42]. Increased tankyrase activity decreases SH3BP2 protein levels.…”
Section: Discussionmentioning
confidence: 99%